Correlação das características macroestruturais com as propriedades elétricas e mecânicas das ligas de al- 0,5% e 1,5% ni tratadas termicamente à 280 °c e 400 °c - MARQUES, Luane Luiza Pereira (2023)
Electricity consumption is present in several segments in the country and is a fundamental system for the functioning of the technological world. In this way, it becomes interesting for the industrial sector to improve the electricity distribution network, because due to the large territorial extensions of the country and the bad weather, intense scrapping of transmission lines occurs. Faced with this reality, this study was carried out with the aim of studying the influence of macrostructures on the electrical and mechanical properties of Al-0,5% and 1,5% Ni alloys heat treated by annealing at 280 °C and 400 °C in time intervals from 1 to 4 hours. The alloys were cast by the conventional method, then samples were taken for chemical and macrostructural analysis of the alloys, the rest of the material was machined to reduce the diameter from 22 mm to 18,5 mm, later laminated to produce wires with a diameter of 3 mm, then samples were separated to carry out the annealing heat treatment, at the following temperatures: 280 °C for 1 hour, 280 °C for 4 hours and 400 °C for 4 hours, after these processes the samples were submitted to a test of electrical conductivity and mechanical strength. The results obtained in the chemical analyzes demonstrated that the manufactured alloys are close to the values of 0,5% and 1,5% of nickel established for this study. The macrostructures revealed that the Al-0,5%Ni alloy had a mixed morphology with chilled, columnar and equiaxed grains, unlike the Al-1,5%Ni alloy, which had a greater presence of equiaxed grains. The electrical conductivity test revealed that the heat treatment was effective, as there was an increase in electrical conductivity as a function of the temperature increase, highlighting that the best results were for the alloy with 0,5% Ni. However, when evaluating the results of the tensile test, it is noted that the heat treatment was not satisfactory, as there was a decrease in the tensile strength limit (TRL) in both alloys because of the increase in temperature, suggesting that the material after heat treatment becomes less resistant and more ductile. It is concluded that for the use of wires for energy transmission cables, the heat treatment was not effective, since the losses in the LRT were above 10%, being outside the standards required by the COPEL protocol.